Firm Value By Good Corporate Governance, Profitability, And Financial Distress In Energy Sector Companies - Muslih, Muhamad; Pratiwi, Dita Indah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Energy sector companies experienced a decline in share prices, which made the company's value also decrease in 2019. The average share price of energy sector companies in 2019 decreased to 1,248/share from 1688/share in 2018. The success of a manager in managing the resources of the company is viewed by investors as the firm value, which is typically linked to stock prices. This study aims to determine the effect of good corporate governance, profitability, and financial distress on firm value. The objects of this research are energy sector companies listed on the Indonesia Stock Exchange for the 2018–2021 period. Based on several criteria in determining the sample, 53 company samples, or 212 data points, were obtained. Analysis of research data using panel data regression using Eviews 12 software. The results showed that good corporate governance, profitability, and financial distress simultaneously affect firm value. However, partially due to the good corporate governance variable, profitability has no effect on firm value, while the financial distress variable has a significant positive effect on firm value.